Effectiveness of Audio-Visual Media on the Four Aspects of Complementary Feeding Education in Pregnant Women to Prevent Stunting - Yuli Admasari; Sarliana Sarliana; Linda Linda (Poltekkes Kemenkes Palu, 2025)
Background: Indonesia has the third-highest stunting rate in Southeast Asia, with inadequate of complementary feeding contributing to the issue. Enhancing pregnant women's knowledge and attitudes about proper complementary feeding is crucial, and research shows that audio-visual media is more effective for education than other formats. This study aimed to compare the effectiveness of audio-visual educational media and leaflets in educating pregnant women about the four conditions (namely timely, adequate, safe, and properly fed) for giving complementary feeding. Methods: This study utilized a quasi-experimental design with a post-test-only control group. Data was collected from 40 Biromaru Community Health Center pregnant women from August to September 2023. The analysis utilized frequency distribution and the Mann-Whitney test. Results: The average knowledge (24.58) and attitude (25.88) of the audio-visual media group was higher than the knowledge (16.43) and attitude (15.13) of the leaflet media group. P value=0.02(<0.05) for the knowledge variable and p=0.01(<0.05) for the attitude variable Conclusion: Audio-visual media is more effective than leaflets in improving knowledge and attitudes about the four complementary feeding requirements to prevent stunting in pregnant women. It can serve as an alternative educational tool for health workers during pregnant women's classes.